2021
DOI: 10.1371/journal.pone.0246115
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal congestion mouse model: Could it serve as a pachychoroid model?

Abstract: Pachychoroid spectrum diseases have been described as a new clinical entity within the spectrum of macular disorders. “Pachychoroid” is defined as choroidal thickening associated with dilated outer choroidal vessels often showing retinal pigment epithelium (RPE) degeneration. Although various clinical studies on the pachychoroid spectrum diseases have been conducted, the pathophysiology of pachychoroid has yet to be fully elucidated. In this study, we attempted to establish a mouse model of pachychoroid. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The CCFA ratio and CV of the CCFA ratio were more significantly impaired in AMD fellow eyes with asymmetric choroidal vasculature than in those without. Asymmetry in the choroidal vasculature is reportedly caused by congestion in the choroidal vortex veins [ 18 , 37 ], followed by an increased outflow resistance in the sclera [ 48 , 49 , 50 , 51 ]. An imbalance in the large choroidal vascular flow may have affected the balance of the overall choroidal flow, which could cause a reduction in choriocapillaris flow, in a heterogenous manner, as has been shown in the current study ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CCFA ratio and CV of the CCFA ratio were more significantly impaired in AMD fellow eyes with asymmetric choroidal vasculature than in those without. Asymmetry in the choroidal vasculature is reportedly caused by congestion in the choroidal vortex veins [ 18 , 37 ], followed by an increased outflow resistance in the sclera [ 48 , 49 , 50 , 51 ]. An imbalance in the large choroidal vascular flow may have affected the balance of the overall choroidal flow, which could cause a reduction in choriocapillaris flow, in a heterogenous manner, as has been shown in the current study ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…After passing through the choriocapillaris, blood passes through a network of venous collecting vessels that drain into the vortex veins, which are normally distributed throughout the eye with 1 to 2 located in each quadrant, a pattern that is similar in mice and in humans. 44 Whole-mount staining revealed that while the expected distribution of vortex veins was observed in the choroids of control mice, vortex vein patterning was disrupted in Angpt1 ΔNC mice and only 2 veins were observed in the majority of mutant eyes (Figure 4A and 4B, Mean number of vortex veins per eye, Control: 4.13±0.07, Angpt1 ΔNC: 2.19±0.15, P <0.0001). Vortex vein patterning appeared fixed at birth, and reduced vortex vein number was observed in mutant animals at timepoints ranging from P0-adulthood (Figure 4B).…”
Section: Resultsmentioning
confidence: 89%
“…10 Experimental occlusion of vortex veins rapidly results in choroidal congestion, dilated choroidal vessels and a phenotype resembling pachychoroid. 44,67 Further suggesting that vortex vein dysfunction may underlie pathogenesis of CSC and other pachychoroid diseases, obliteration of distinct watershed zones by intervortex anastomoses, which are rare in normal eyes, is widespread in pachychoroid. 7,[12][13][14][15]68 Here, using neural crest-specific Angpt1 knockout mice, we have demonstrated that ANGPT1 is essential for embryonic patterning of the vortex veins.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this hypothesis, we created vortex vein congestion in the mouse eye as a possible pachychoroid model by ligating the vortex veins outside the sclera [ 16 ]. In this mouse model, choroidal thickening associated with dilatation of choroidal vessels, as seen in pachychoroid spectrum diseases, was observed after vortex vein congestion became established.…”
Section: Introductionmentioning
confidence: 99%